Characterization of Ceramic Materials Synthesized by Mechanosynthesis for Energy Applications - Cortés-Escobedo, Claudia A.; Jesús, Félix Sánchez-De; Torres-Villaseñor, Gabriel; Muñoz-Saldaña, Juan; Bolarín-Miró, Ana M. (IntechOpen, 2012)
None